MOTIVASI DUGEM REMAJA PARTY GOERS DI KOTA BATAM - Kasih Purwati; Cevy Amelia (Universitas Batam, 2019)
Changes that are so rapid in the city of Batam, inevitable changes in people's behavior, especially with the global competition makes Batam city continue to strive to continue to make changes that make people continue to be encouraged. Teenagers play a role in this, but it is unfortunate that teenagers today only want to live for pleasure. Many teenagers look for an entertainment place for them, one of the places that become the area of teenagers is a clubbing. Batam city is a city that is located close to neighboring Singapore. It has a very exotic night, which will make teenagers will be entertained and dissolved things that make them happy and can forget the problems they are facing. The purpose of this study was to determine the motivation of clubbing teenage party-goers in Batam City. this research is a qualitative descriptive study. The subjects in this study were 2 teenage party-goers in Batam City, aged 22-23 years who have a clubbing hobby ranging from 2-4 times a week. Retrieval of data in this study using the interview method. Intrinsic motivation is the basis of each research subject when doing clubbing activities that are based on the problem factors they face to get entertainment and pleasure because they feel tired and burdened with the work and lectures they live. Meanwhile, extrinsic motivation arising from clubbing activities they do result from the influence of invitations of others and the element of avoiding punishment for not wanting to be considered as people who are not loyal friends. From the results of the interview, it was obtained that the motivation of clubbing teenagers in party-goers in Batam was rooted because there was an intrinsic motivation and extrinsic motivation.